The Implementation Of Madrasah Education Administration In The 5.0 Society Era - Hamdanah Hamdanah (STAIFAS-Press, 2022)
Abstract The era of society 5.0 is an era of digitalization that is all practical if humans can make the best use of the available technology. This era is centered on people and technology. In this era of society 5.0, many conveniences can be used to facilitate work in all fields, including education. The objectives of education in a madrasa can be realized by implementing a well-implemented educational administration. With the implementation of good administration in the era of society 5.0, it will provide educational services as much as possible. In this study, researchers used a phenomenological design that aims to see the form of service by implementing educational administration in the era of society 5.0 in Madrasah using techniques or research methods of observation, interviews, and documentation. Observations and interviews were conducted to observe and find out the implementation of educational administration carried out in madrasahs in the era of society 5.0. The results of the study found that educational administration is implemented by utilizing all the conveniences available in the era of society 5.0 with humans controlling the technology, but still, the role and function of humans in education administration cannot be replaced by AI.